Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Answer:
Step-by-step explanation:
[tex]\sqrt{(x + 2)(x - 3)} = 0 \\\\ (x + 2)(x - 3) = 0 \\\\\ x^2 - 3x + 2x - 6 = 0 \\\\ x^2 - x - 6 = 0 \\\\ \Delta = (- 1)^2 - 4.1.(- 6) \\\\ \Delta = 1 + 24 \\\\ \Delta = 25 \\\\ x_1 = \frac{1 + \sqrt{25}}{2} = \frac{ 1 + 5}{2} \\\\\ x_1 = 3 \\\\\\ x_2 = \frac{1 - \sqrt{25}}{2} \\\\\\ x_2 = \frac{1 - 5}{2} \\\\\ x_2 = - 2[/tex]
S = {x E R/x = 3 and x = - 2}
I hope I've helped you
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.